A retrospective evaluation of zirconia-fixed partial dentures in general practices: An up to 13-year study. Issue 2 (February 2015) - Håff, Anna; Löf, Hanna; Gunne, Johan; Sjögren, Göran
Highlights Ninety-four percent of the Y-TZP FPDs evaluated performed satisfactorily. The survival rate of the Y-TZP FPDs was within the same range as for metal–ceramic FPDs. For plaque and bleeding no significant differences were seen compared with the controls. Based on a visual analog scale patient satisfaction with the evaluated FPDs was high.